Fuzzy multicriteria evaluation of health research investments - Kahraman, Cengiz; Süder, Aslı; Kaya, İhsan (Technological and Economic Development of Economy, 2014)
Health research and investments are expensive, and its explicit social, health and economic impacts are hard to define. There are many challenges and assumptions in defining specific returns on investment in health research. In the literature, there is no common approach to evaluate health research impacts. Single criterion methods are generally used with validated indicators to track overall outcomes or outcomes in a specific health research area. These methods have the ability of considering only one criterion at a time, which is usually the cost of the investment. A multicriteria method is proposed for taking care of many conflicting criteria of health research investments. The difficulty of measuring intangible criteria is captured by the fuzzy set theory. Fuzzy analytic hierarchy process (AHP) is used for the selection among four possible health research investment alternatives. A sensitivity analysis is made for the changes in the values of various parameters.First published online: 05 Feb 2014